A self-recovering RAKE receiver for asynchronous CDMA systems - Torlak, M.; Evans, B.L. (2000 IEEE International Conference on Acoustics, Speech, and Signal Processing. Proceedings (Cat. No.00CH37100), 2000)
In asynchronous CDMA systems, transmission over frequency-selective channels subjects the signal to interchip interference and intersymbol interference, both of which cause multiple access interference (MAI). MAI cannot be easily eliminated without the knowledge of the channel parameters. Both blind adaptive and subspace based multiuser receivers have been proposed to eliminate the interference. We propose a self-recovering RAKE receiver that does not require training sequences or knowledge of interfering user signature waveforms. The contribution of this paper is the combination of constant modulus algorithm and previously derived constrains. The constrains depend on the multipath structure of the desired signal. The proposed receiver converges faster than the blind adaptive multiuser receivers. Its fast convergence and low complexity make it well suited for rapidly time-varying mobile radio frequency selective fading channels. By simulation, we compare the proposed method with blind adaptive constrained LMS RAKE receiver and minimum output energy receiver.